Discovery of Chemoselective and Biocompatible Reactions Using a High‐Throughput Immunoassay Screening1. Issue 46 (7th October 2013) - Kolodych, Sergii; Rasolofonjatovo, Evelia; Chaumontet, Manon; Nevers, Marie‐Claire; Créminon, Christophe; Taran, Frédéric
<x xml:space="preserve">Abstract</x> An immunoassay‐based method was used to screen numerous combinations of dipoles and dipolarophiles for their ability to undergo chemoselective and biocompatible [3+2] cycloaddition reactions. The approach fulfills most of the requirements of the click concept and led to the discovery of a copper‐catalyzed reaction that generates pyrazoles from sydnone and alkyne reagents.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>